ANALISIS KEPUASAN KONSUMEN PRODUK RENGGINANG PADA USAHA INDUSTRI RUMAH TANGGA FATIH RENGGINANG KECAMATAN SEI SUKA KABUPATEN BATU BARA - Siti Fauziah Sari; Yenni Mariani Sinurat (GEMILANG: Jurnal Manajemen dan Akuntansi, 2022)
This study aims to determine the consumer satisfaction of rengginang products in the home industry business, Sei Suka District, Batu Bara Regency. The subjects of this study were consumers of Fatih Rengginang, Sei Suka District, Batu Bara Regency, which amounted to 10 people. Data collection methods are interviews, observations and field studies, while the data analysis methods used are data reduction, data display and conclusion drawing/verification. The results of this study indicate that the home industry business Fatih Rengginang produces in various sizes with various prices and affordable prices and the quality of taste is delicious and savory and based on the results of the analysis shows that there is a high level of satisfaction with service quality and product quality. in the high category, this is shown from the results of interviews with consumers of Fatih Rengginang.